Exploring Sayyid Qutb's Wasatiyyah Concept in Tafsir Fi Zhilal Al- Qur'an: Implications for Religious Moderation in Indonesia - Fauziah, Debibik Nabilatul; Zulaiha, Eni; Yunus, Badruzzaman M.; Muhyiddin, Asep (UIN Sunan Gunung Djati Bandung, 2025)
The term wasaṭiyyah comes from the sentence